2020
DOI: 10.1186/s12875-020-01126-9
|View full text |Cite
|
Sign up to set email alerts
|

Management in primary care at the time of a suicide attempt and its impact on care post-suicide attempt: an observational study in the French GP sentinel surveillance system

Abstract: Background: We aimed to describe primary care management at the time of a suicide attempt (SA) and after the SA. Methods: An observational (cross-sectional) study was conducted among 166 sentinel GPs within France (a nongatekeeping country) between 2013 and 2017 for all GP's patients who attempted suicide. Measurements: frequency of patients 1) managed by the GP at the time of the SA, 2) addressed to an emergency department (ED), 3) without care at the time of the SA, and 4) managed by the GP after the SA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Michaud et al (2021) illustrate how individuals who have attempted suicide appreciate the nurse's professional involvement in their aftercare, and they also appreciate more meetings and more follow-up calls. Younes et al (2020) mention how GPs become more involved in the individual's care after a suicide attempt. Individuals who attempt suicide place value on staff who are committed, both humanly and professionally (Michaud et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Michaud et al (2021) illustrate how individuals who have attempted suicide appreciate the nurse's professional involvement in their aftercare, and they also appreciate more meetings and more follow-up calls. Younes et al (2020) mention how GPs become more involved in the individual's care after a suicide attempt. Individuals who attempt suicide place value on staff who are committed, both humanly and professionally (Michaud et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For each reported case, GP provide descriptive data. Collected data evolve according to research interests and context [ 27 , 31 , 33 , 34 ]. The data included sociodemographic characteristics, history of previous attempts, the method used for the suicidal act, the vital outcome (whether the patient survived or died), and the characteristics of the last consultation in primary care (date, reasons, exploration, and expression of suicidal ideation).…”
Section: Methodsmentioning
confidence: 99%
“…Among them, 37.7% reported visiting a doctor or a psychiatrist/psychologist. Another study showed that French GPs were more likely to be involved in the management of the patient at the time of the SA if the patients were younger [ 27 ]. This may have been exacerbated during the pandemic due to hospitals being overwhelmed or the fear of going to the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…In some countries, ED referrals are made primarily to GPs ( Fleischmann et al, 2005 ), and evidence shows that GPs are highly involved in the care of their suicidal patients ( Boffin and Van Casteren, 2018 ). GPs are often the first health professional seen after a suicide attempt ( Younes et al, 2020 ), and they frequently see people within 1 week of hospital discharge following a suicide-related admission ( Gunnell et al, 2002 ). As most studies only documented if an individual had a health service contact, and not the number or types of health service contacts received, the overall level of support and aftercare people received could also not be determined.…”
Section: Strengths and Limitationsmentioning
confidence: 99%